Pembatalan Akta Pencatatan Sipil Menurut Pasal 72 Undang-Undang Nomor 23 Tahun 2006 Tentang Administrasi Kependudukan: Cancellation of Civil Registration Deed according to Article 72 of Law Number 23 of 2006 concerning Population Administration - Napitupulu, Joshua Michael Ferdinando (Brawijaya Law Student Journal, 2022)
Joshua Michael Ferdinando Napitupulu, Amelia Sri Kusuma Dewi, Suhariningsih Fakultas Hukum Universitas Brawijaya Jl. MT. Haryono No. 169 Malang e-mail: joshuaferdinando@gmail.com Abstract This research aims to analyze the regulation concerning the cancellation of a civil registration deed. Article 72 of Law Number 23 of 2006 concerning Population Administration does not meet the matter of legal certainty which occurs due to inappropriate placement of phrases, resulting in meanings that actually distort the rules rather than the purpose for which the rules were made, while Law number 12 of 2011 concerning Legislation Making implies that the principle of legal certainty must be set forth in every law enforced. This research employed a normative method that obtained the research data from books and the law related to Article 72 of Law Number 23 of 2006 concerning Population Administration as literature resources. With conceptual and statutory approaches, this research used legal materials from varied resources, including the law as the primary material, supported by books, scientific journals, law writing, or the notions of experts published in mass media. Data were collected based on library research and analyzed with grammatical and systematic analysis methods. This research reveals that there is a legal loophole in Article 72 of Law Number 23 of 2006 concerning Population Administration. Keywords: Deed, Civil Registration, Population Documents, Legal Certainty Principle Abstrak Penelitian ini bertujuan untuk menganalisis peraturan mengenai pembatalan akta pencatatan sipil. Pasal 72 Undang-Undang Nomor 23 Tahun 2006 tentang Administrasi Kependudukan tidak memenuhi soal kepastian hukum yang diakibatkan oleh penempatan frasa yang tidak tepat sehingga menghasilkan pemaknaan yang justru menyimpangkan aturan tersebut daripada tujuan dibuatnya peraturan tersebut, sedangkan Undang-Undang nomor 12 Tahun 2011 tentang Pembentukan Peraturan Perundang-undangan mengandung makna bahwa asas kepastian hukum harus dituangkan dalam setiap penegakan hukum. Penelitian ini menggunakan metode normatif yang memperoleh data penelitian dari buku-buku dan undang-undang terkait Pasal 72 Undang-Undang Nomor 23 Tahun 2006 tentang Administrasi Kependudukan sebagai sumber literatur. Dengan pendekatan konseptual dan perundang-undangan, penelitian ini menggunakan bahan-bahan hukum dari berbagai sumber, termasuk hukum sebagai bahan utama, didukung oleh buku-buku, jurnal ilmiah, tulisan hukum, atau pemikiran para ahli yang dimuat di media massa. Data dikumpulkan berdasarkan penelitian kepustakaan dan dianalisis dengan metode analisis gramatikal dan sistematik. Penelitian ini mengungkap adanya celah hukum pada Pasal 72 Undang-Undang Nomor 23 Tahun 2006 tentang Administrasi Kependudukan. Kata Kunci: Akta, Pencatatan Sipil, Dokumen Kependudukan, Asas Kepastian Hukum